In Silico Study: Potential Prediction of Curcuma longa And Cymbopogon citratus Essential Oil As Lipoxygenase Inhibitor - Bare, Yohanes; Indahsari, Lilin Ika Nur; Sari, Dewi Ratih Tirto; Watuguly, Theopilus (JSMARTech, 2021)
Abstract: Inflammation is the human body response by the injure as a results the inflammation will release LOX. To curve the conditions we use the bioactive from the nature are essential oil from Curcuma longa and Cymbopogon citratus because has a potential has pharmacologist activity. The purpose of this research to investigate the role essential oil from Curcuma longa and Cymbopogon citratus through LOX gene. Several chemical substances, including 3,7-dimethyl-1,3,6-octatriene, camphor, eugenol, curzerene and isoborneol were retrivied from PubChem database. The PyRx 0.8 was used to minimize and convert the sdf file to pdb format file of ligands. Those compounds were predicted their interaction using STITCH online server. Ligands and protein were docked by HEX Cuda 8.0.0 program, 3D and 2D views were evaluated using Discovery studio ver.19.0.0 and LigPlot+ ver 2.2, respectively. We found fourteen amino acid residues from LOX which bound the chemical compounds. Those interaction was supported by hydrogen bond with variety energy binding. To sum up, the essential oil from Curcuma longa and Cymbopogon citratus has a potential function as inhibitor LOX by inhibiting fourteen active side of the LOX gene.Â